Raised Serum Homocysteine Level is Associated with Coronary Artery Disease in Young Patients - R, Begum; MMA, Bhuiyan; S, Ferdoushi; KA, Rahim; DK, Adhikari; SMR, Rahman; AK, Pramanik; AKMS, Rahman; FI, Khan; MC, Nath; et al. (Archives of Clinical and Biomedical Research, 2022)
Background: Coronary artery disease (CAD) is increasingly prevalent among young population. High serum homocysteine level has been suggested as a risk factor for atherosclerosis leading to CAD. This study was aimed to evaluate serum homocysteine level in young and adult patients with coronary artery disease. Methods: This cross-sectional study was conducted at the Department of Laboratory Medicine, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from March 2021 to February 2022. A total of 52 patients with coronary artery disease were included. Among them 26 were young patients (age <40 years, group I) and 26 were adults (age ≥40 years, group II). Their relevant history, clinical examination findings and risk factor profiles were noted accordingly. Serum homocysteine level was estimated by automated immunoassay analyzer with the principle of chemiluminescent microparticle immunoassay (CMIA). Data were analyzed and compared by statistical tests. Results: Male patients were predominant in both groups. Regarding risk factors, smoking habit and diabetes mellitus had significant difference between young and adult individuals having CAD (p<0.05). It was observed that mean(±SD) serum homocysteine level was significantly higher in young patients than adults (21.93±7.56 μmol/L versus 12.04±5.33 μmol/L, p <0.001). Moderate hyperhomocysteinemia and intermediate hyperhomocysteinemia was significantly present in group I than group II (69.2% versus 15.4% and 30.8% versus 0.0%, p <0.001). Conclusion: Serum homocysteine level is significantly higher in young patients than adult patients with coronary artery disease. Therefore, high level of serum homocysteine may be used as early detection and disease evaluation